2021
DOI: 10.1186/s13068-021-01894-1
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of oxidation–reduction potential and hydrogen peroxide concentration as tools for revealing LPMO inactivation during enzymatic saccharification of cellulose

Abstract: Background Biochemical conversion of lignocellulosic biomass to simple sugars at commercial scale is hampered by the high cost of saccharifying enzymes. Lytic polysaccharide monooxygenases (LPMOs) may hold the key to overcome economic barriers. Recent studies have shown that controlled activation of LPMOs by a continuous H2O2 supply can boost saccharification yields, while overdosing H2O2 may lead to enzyme inactivation and reduce overall sugar yields. While following LPMO action by ex situ ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…The progress curve shows that product formation diminished after a fast and linear initial phase. This is indicative of enzyme inactivation, which is to be expected in experiments with high amounts of added H 2 O 2 [24,56,57].…”
Section: Resultsmentioning
confidence: 86%
“…The progress curve shows that product formation diminished after a fast and linear initial phase. This is indicative of enzyme inactivation, which is to be expected in experiments with high amounts of added H 2 O 2 [24,56,57].…”
Section: Resultsmentioning
confidence: 86%
“…Although H 2 O 2 is used efficiently in polysaccharide peroxygenase reaction, a reductant peroxidase side reaction may lead to the irreversible inactivation of LPMOs by H 2 O 2. ,,,, Indeed, our recent results demonstrated that cellulose-free Tr AA9A can perform an average of 138 ascorbic acid peroxidase reactions before complete inactivation of the enzyme . Therefore, a fine-tuned control over the levels of H 2 O 2 is a prerequisite for the maintenance of LPMO stability.…”
Section: Discussionmentioning
confidence: 97%
“…14,35,50 A study by Kadic et al demonstrated that the optimal H 2 O 2 supply rate for anaerobic degradation of cellulose (Avicel at 50 g L −1 ) by the enzyme cocktail (Cellic CTec3) was around 50 μM h −1 , whereas supply rates of 100 μM h −1 and above were deleterious for the LPMO activity. 50 In aerobic conditions, H 2 O 2 is also formed in reactions between O 2 and compounds in pretreated biomass. 38 While O 2 diffusion may be potentially rate-limiting under high dry matter conditions of lignocellulose saccharification, the experiments used here for the measurement of the rates of H 2 O 2 production were set up so that the O 2 diffusion was not rate-limiting (Figure S5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the values of the kinetic parameters and their dependency on cellulose concentration suggest that the flow of H 2 O 2 through the cellulolytic peroxygenase reaction is strongly favored over side reactions. However, because the contact times required to achieve target conversion are usually in the range of 72 to 96 h ( 55 ), the stability of LPMOs is a major issue in the application of these enzymes in lignocellulose conversion ( 24 , 56 ). Our results suggest that LPMOs and their variants with low efficiency of the reductant peroxidase reaction and low probability of enzyme inactivation should be more stable.…”
Section: Discussionmentioning
confidence: 99%